ناسنامەی کۆمەڵایەتی لای خوێندکاری زانکۆ: توێژینەوەیەکی مەیدانییە لە زانکۆکانی شاری سلێمانی - رسول, پ.ی.د.عزالدین عبدالصمد; احمد, کاظم محمد زاهد (Sulaimani Journal for Humanities, 2023)
Identity has become a major characteristic of the individual, especially adolescence and university in society. Social identity itself emphasizes the cultural and social framework in terms of appearance and formation, long-term and continuously affects most different aspects of the individual in other stages of life. It depends on the type and style of identity he has created for himself in his life. The main purpose of this study is to present a measure of the level of social identity among university students. The method used is quantitative through the use of questionnaire tools, and the research community is the universities of Sulaimani and the size of the participants is (400) students of both genders, by multistage randomization the sample has been selected, the research was conducted between 19th/Oct/2022 to 1st/Dec/2022. The results of the study show that the most important measure of social identity among university students is the philosophy of life and leisure initially, then friendship and family and finally the field of behavior with the opposite gender, also shown in the fields (family, friendship and philosophy of life). There is no statistically significant difference between men and women in terms of family, friendship and life philosophy, but in terms of behavior with the opposite gender there is a documented statistical difference between males and females, the reason for this difference is due to male gender. There is also a statistically significant difference between public and private universities in terms of family and social identity, the reason for this difference is private universities. There is a statistically significant difference between urban and suburban residents in the field of family. However, there is no statistically significant difference between suburban and urban residents in the areas of friendship, philosophy of life, and treatment of the opposite gender.
Keywords: identity; social identity; structure of identity; university students; Sulaymaniyah city